Effects of plant invasion on arbuscular mycorrhizal fungi -- a review of how these community dynamics are studied - Curland, Rebecca (My University, 2009)
Arbuscular mycorrhizal fungi (AMF) are vital components in most plant communities and therefore in almost all terrestrial ecosystems. Historically, AMF symbioses have been observed through microscopy and spore isolation. Given advancements in molecular technologies over the last couple of decades, ecologists are now able to observe AMF community dynamics in a more complex way, thereby broadening the understanding of the scope of ecological interactions concerning AMF. One area of interest are the effects exotic plant invasions have on native AM fungal communities and consequently on native plant communities. Over the last 20 years there have been some interesting studies published indicating that the introduction of invasive alien plants has significant ecological impacts on native AMF populations. In this paper, I will examine the ecology ofAMF and exotic plant invasion. Specifically, I will consider study design, previous research, molecular methods, data interpretation, limitations of AMF ecology technology and the future of AMF invasive ecology.
Keywords: Vesicular-arbuscular mycorrhizas -- Ecology